Application of interactive dam safety decision support system (INSPiRE) for flood emergency response plan (ERP) of sultan abu bakar dam malaysia - Sidek L.M.; Basri H.; Mohiyaden H.A.; Said N.F.M.; Yalit M.R.; Basri H.; Muda R.S. (Emerald Group Publishing Ltd., 2023)
Flood Emergency Response Plan (ERP) is a plan that guides responsibilities for proper operation of Sultan Abu Bakar (SAB) dam in response to emergency incidents affecting the dam by high water storage capacity. Based on this study, four major responsibilities are needed for SAB dam owing to protect any probable risk for downstream which can be Incident Commander, Deputy Incident Commander, On-scene Commander and Civil Engineer. Having organisation charts based on ERP exercise can be helpful for decreasing the probable risks in any projects such as Abu Bakar Dam and it is a way to identify and suspected and actual dam safety emergencies. A dam safety emergency is an event, which could potentially lead to dam break and need to be taken care of a massive plan. To mitigate the hydro hazard due to dam break, UNITEN has developed a new application software known as INSPiRE (Interactive Dam Safety Decision Support System). INSPiRE, as an intelligent dam safety software, is developed to address emergencies, which demand fast, decision making and effective multi-agency collaboration due to SAB dam break event. INSPiRE will contribute towards the sustainability of SAB dams owner as corporate reputations can be ruined through dam structural failures that can affect the economy of the nation and enhance the quality of life of the people. 2019 by Emerald Publishing Limited All rights of reproduction in any form reserved.